ANALISIS ASPEK TINDAK PIDANA KORUPSI PENERBITAN SERTIFIKAT HAK MILIK ATAS TANAH NEGARA - Putra, Suardi Rahman; Rodliyah; Rina Rohayu Harun (LPPM STIH Awang Long, 2023)
This research aims to analyze the modus operandi of Corruption in the Issuance of Land Ownership Certificates for State Land and to analyze the considerations of judges in sentencing for Corruption in the Issuance of Land Ownership Certificates for State Land based on the verdict of the Mataram District Court Number 32/Pid.Sus.TPK/2017/PN.Mtr. The problem of corruption in Indonesia is spreading across all aspects of life and requires serious attention from the government, especially in preventing its further proliferation. A corruption case occurred in East Lombok Regency, specifically in Sekaroh Village, Keruak Sub-district. In this case, the defendants, who were Civil Servants in the Land Office of East Lombok Regency, were found guilty of committing corruption under Article 3 of Law Number 31 of 1999 Jo. Law Number 20 of 2001 concerning the Eradication of Corruption, as they abused their authority to issue land ownership certificates within the Sekaroh forest area. The research adopts a qualitative normative approach. The researcher focuses on the corruption case in the Mataram District Court, Case Number 32/Pid.Sus.TPK/2017/PN.Mtr. The research method used is normative/legal doctrinal research, combining normative legal approach with the addition of various empirical elements. Abuse of position or authority is an act of using the authority possessed to favor or discriminate in favor of a group or individual while being discriminatory against other groups or individuals. In the legislation regarding corruption, the element of